1975
DOI: 10.1159/000158060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neomycin on <sup>45</sup>Ca Binding and Distribution in Canine Arteries

Abstract: The effects of neomycin (7.0 mM) on 45Ca movements and distribution were investigated in canine aortae and in canine carotid and terminal mesenteric arteries. Uptake of 45Ca was measured in calcium-free solution; the 45Ca tissue spaces in the carotid and terminal mesenteric arteries were 2–4 times greater than those observed in the aorta. Exposure of the aortae and the terminal mesenteric arteries to 1.5 mM Ca++ during the washout elicited large increases in 45Ca eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1978
1978
1987
1987

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…If present findings with an isolated heart muscle model relate to other excitable tissues, then an interference by aminoglycoside antibiotics with Ca++ influx across cell membranes may well explain the depressant properties of these drugs previously observed in a variety of functionally related and unrelated tissues in both man and lower animals (1)(2)(3)(4)(5)(6)(7)(8)(9). Importantly, present observations also provide a mechanistic explanation for cardiac irregularities occasionally detected in patients treated with aminoglycoside antibiotics (4,(21)(22)(23).…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…If present findings with an isolated heart muscle model relate to other excitable tissues, then an interference by aminoglycoside antibiotics with Ca++ influx across cell membranes may well explain the depressant properties of these drugs previously observed in a variety of functionally related and unrelated tissues in both man and lower animals (1)(2)(3)(4)(5)(6)(7)(8)(9). Importantly, present observations also provide a mechanistic explanation for cardiac irregularities occasionally detected in patients treated with aminoglycoside antibiotics (4,(21)(22)(23).…”
Section: Resultsmentioning
confidence: 62%
“…On the other hand, La... displaces and replaces Ca++ at various superficial membrane sites, thereby reducing net availability of Ca++ for translocation (17,19). We have previously reported that aminoglycosides decrease the uptake and increase the efflux of 45Ca in vascular smooth muscle by affecting superficial membrane sites and, through this Ca++-dependent action, inhibit contractile responses of arteries to a variety ofvasoconstrictor agents (5,6,20). Based on present mechanical findings, it seems that gentamicin also disrupts the excitationcontraction coupling process in heart muscle, perhaps by inhibiting the binding of Ca++ at superficial membrane sites responsible for availability of Ca++ for transsarcolemmal systolic influx.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies the uptake of 4sCa in vascular smooth muscle was markedly inhibited by gentamicin (3) and by other aminoglycoside antibiotics (14,17). Under these conditions, it was postulated that aminoglycoside antibiotics interfere with the uptake and/or binding of a specific fraction of Ca2+ and, in this manner, may alter the ability of vascular smooth muscle to respond to stimulatory agents (3,17).…”
Section: Discussionmentioning
confidence: 88%
“…In selected iso lated arterial smooth muscle preparations from dogs, rabbits and different nonhuman primate species, it was found that the aminoglycoside antibiotics interfere with excitation-contraction coupling in vascular smooth muscle by preventing reuptake or rebinding of Ca2+ at specific superficial cellular sites (3,13,14,17). Furthermore, in vascular preparations in which contractile responsiveness was highly dependent upon superficially bound Ca2+, neomycin had a stronger inhibitory effect (2,14). This type of an effect would be expected if an agent acted primarily at relatively superficial calcium sites or stores.…”
mentioning
confidence: 99%